Study on Anti_ Candida Effects of Essential Oil and Extracts of Iranian Medicinal Plants, In vitro - A Naeini; M Naseri; M Kamalinejad; F Khoshzaban; T Rajabian; H Nami; S Mansori; D Zavieh (Institue of Medicinal Plants, ACECR, 2011)
Background: Candidiasis is a primary or secondary mycotic infection caused by members of the genus Candida. Objective: Recently fungal infections especially Candidiasis has significantly increased. Limitations in treatment of fungal diseases include a few available anti-fungal drugs, side effects, drug resistance and decreased susceptibility of Candida species to anti-fungal drugs, leads to search for new anti-fungal agents as herbal medicines. Methods: 17 essential oils and 172 plant extracts, from 50 Iranian plant species obtained through the literature and interviews with traditional healers, were evaluated for Anti _Candida activity. The essential oils and extracts were tested by disc diffusion against Candida albicans (ATCC=10231). Amphotericin B, Ketoconazol and Nistatin were used as positive controls. Results: Sixteen (32%) out of the 50 plants were found to be active. The essential oils of Thymus kotschyanus, Zataria multiflora Boiss, Artemisia sieberi, Mentha spicata, Satureia hortensis, Lavandula angustifolia and Cuminum cyminum showed high strong activity. The essential oils of Nigella sativa and Rosmarimus officinalis and Myrtus communis showed strong activity. The essential oils of Eucalyptus globulus, Pimpinella anisum, foeniculum vulgare, Heracleum persicum, showed intermediate activity. Conclusion: The results of this investigation showed a potent anti_candida activity of selected herbs against Candida albicans type strain. Therefore further investigation need in order to isolate and identify the active compounds to make it available for clinical use.